2017
DOI: 10.7759/cureus.1633
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Drug Interaction between Ticagrelor and Statin Leading to Acute Renal Failure

Abstract: Dual antiplatelet agents and high-intensity statins are frequently used in combination after myocardial infarction. Ticagrelor has the potential of causing acute kidney injury. Rosuvastatin is excreted through the kidneys and dose adjustment is needed in patients with kidney disease. When used in combination, they can potentiate the toxic effects of each other. We report a case of drug interaction between rosuvastatin and ticagrelor resulting in rhabdomyolysis and acute renal failure necessitating dialysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 6 publications
0
16
0
2
Order By: Relevance
“…A possible rosuvastatin-ticagrelor interaction was also reported for a 49-year-old female patient [ 65 ]. Beside 90 mg ticagrelor twice daily and rosuvastatin 20 mg, the patient was treated with lisinopril 20 mg, metformin 500 mg, metoprolol 50 mg twice daily, and pantoprazole 40 mg.…”
Section: Review Of Reported Case Studies With a Possible Ticagrelor-smentioning
confidence: 85%
“…A possible rosuvastatin-ticagrelor interaction was also reported for a 49-year-old female patient [ 65 ]. Beside 90 mg ticagrelor twice daily and rosuvastatin 20 mg, the patient was treated with lisinopril 20 mg, metformin 500 mg, metoprolol 50 mg twice daily, and pantoprazole 40 mg.…”
Section: Review Of Reported Case Studies With a Possible Ticagrelor-smentioning
confidence: 85%
“…A review of literature revealed eleven [14][15][16][17][18][19][20][21][22][23][24] reported cases of ticagrelor induced ARF and rhabdomyolysis (Table 1). 10 cases were found in patients who were also on prescription of high intensity statins with rosuvastatin being the most commonly used statin.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, two more case reports were published. Samuel and collaborators described a case of drug interaction between rosuvastatin and ticagrelor, resulting in rhabdomyolysis and acute renal failure necessitating dialysis in a 49‐year‐old African‐American female . The patient was also taking lisinopril and prior to hospitalization, she attended a rigorous exercise routine at a cardiac rehabilitation centre 3 days per week which resulted in significant weight loss for a couple of months.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism leading to the worsening of renal function by ticagrelor is unknown, but the PLATO trial showed that serum creatinine concentration was increased by more than 30% in 25.5% of the patients receiving ticagrelor. Worsening of the renal function was more pronounced in patients over 75 years of age, in patients receiving angiotensin receptor inhibitors and patients with pre‐existing renal dysfunction . It is speculated that inhibition of adenosine reuptake by ticagrelor reduces glomerular filtration rate through vasoconstriction of the afferent renal arteriole .…”
Section: Discussionmentioning
confidence: 99%